Antiarrhythmic profile and endothelial action of novel decahydroquinoline derivatives - Kozlovski, Valery I; Vdovichenko, Vladimir P; Chlopicki, Stefan; Malchik, Sergey S; Praliyev, Kaldybek D; Zcilkibayev, Oral T (Polish journal of pharmacology, 2004)
We tested antiarrhythmic and endothelial action of novel decahydroquinoline derivatives. Antiarrhythmic activity was analyzed using models of aconitine-, calcium chloride-, and adrenaline-induced arrhythmias in rats. Potency to induce nitric oxide (NO)-dependent coronary vasodilation was assessed in isolated guinea pig heart perfused according to Langendorff technique. Among 15 novel decahydroquinoline derivatives (D1-15), four of them displayed antiarrhythmic activity (D12-D15). D12-D15 compounds were more active in the model of aconitine-induced arrhythmias than in calcium chloride-induced arrhythmias and were inactive in the model of adrenaline-induced arrhythmias. Profile of antiarrhythmic activity of D12-D15 compounds was similar to that of quinidine and procainamide. Interestingly, in the isolated guinea pig heart D14 and D15 (10(-5) M) induced coronary vasodilation, that was mediated by endothelium-derived NO. In conclusion, novel decahydroquinoline derivatives described here (D12-D15) show antiarrhythmic activity typical of antiarrhythmic drugs of class I. Importantly, some of these compounds (D14, D15) release NO from coronary endothelium, which may provide an additional therapeutic benefit.